Liberalization of Trade in Financial Services and Financial Sector Stability (Analytical Approach) - Kireyev, Alexei (IMF Working Papers; Working Paper ;, 2002)
The paper seeks to establish a link between the liberalization of trade in financial services undertaken by countries under the WTO and the stability of their financial systems. The paper concludes that liberalization has generally been conducive to stability because of the mutually reinforcing nature of existing international rules and practices. Financial stability and efficiency, which should be ultimate goals of further liberalization, can be ensured by taking advantage of coherent policy advice and the application of existing multilateral mechanisms-in particular, the WTO negotiations and the IMF/World Bank financial sector assessment program.